Spectrum of Cardiac Arrhythmias During Initial 48 Hours of Acute Myocardial Infarction Patients and their Association with in-Hospital Outcome - Shiram, Syed Ali; Shabbir, Muhammad; Rehman, Waheed Ur; Ali, Jahanzab; Virk, Mutahir Abbas; Mehreen, Sobia; Ahmed, Iftikhar; Imtiaz, Areeba; Azad, Naseem; Chaudry, Azhar Ali (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the spectrum of arrhythmias during initial 48 hours of AMI and their impact on the in-hospital outcome.Study Design: Analytical Cross-sectional study.Place and Duration of Study: This study was conducted at a Tertiary Cardiac Center of Rawalpindi Pakistan from Jun 2021 till Jan 2022.Methodology: A total of (n=150) patients of Acute Myocardial Infarction (AMI) undergoing immediate or early revascularization and meeting the inclusion and exclusion criteria were included in the study. They were monitored for arrhythmias during initial 48 hours of hospitalization and their in-hospital outcomes were noted on a predesigned Performa.Chi square test applied for arrhythmia association with adverse outcome at 95% confidence interval and 5% margin of error.Results: This study comprised (n=117; 78%) males and (n=33; 22%) females. Mean age was 62.9 years. ST elevation MI(STEMI) constituted (n=127; 84.7%) and Non-ST Elevation MI (NSTEMI) (n=23;15.3%) of total patients. Arrhythmias documented in overall (n=122;81.3%) patients, 81.8% (n=104) in STEMI and (n=18; 77.2%) in NSTEMI. Sinus tachycardia(n=52;34.7%) was most common rhythm followed by accelerated idioventricular rhythm (n=20;13.4%) and sinus bradycardia12.7% (n=19). In-hospital mortality was (n=25;16.7%) with p-value=0.009, mostly in patients with ventricular tachycardia/ventricular fibrillation, atrial fibrillationand complete heart block. Other outcomes included (n=23;14.7%) acute left ventricular failure, (n=9; 6%) cardiogenic shock (n=5;3.3%) acute stent thrombosis, (n=2; 1.3%) cerebrovascular accident (CVA)and (n=31; 20.7%) prolonged hospitalization (p-value 0.05).Conclusion: Arrhythmias are common in acute myocardial infarction during initial 48 hours of presentation with sinus tachycardia being most common followed by accelerated idioventricular rhythm and sinus bradycardia. Arrhythmias are associated with increased in-hospital mortality and adverse outcome.